Discussing the Integration and Interconnection of Islamic Sciences (Between Normativity and Historicity) - Ivan Sunata (Pascasarjana UIN Raden Mas Said Surakarta, 2025)
This article discusses the idea of integration and interconnection of Islamic sciences as a response to the dichotomy between religious science and general science among Muslims. Using a normative and historical approach, this research analyzes the relationship between Islamic values and the development of modern science. Integration efforts involve curriculum reconstruction, development of learning models, as well as collaboration between religious scientists and scientific scientists. This article also examines various integration models, such as Syed Naquib al-Attas's concept of the “Islamization of Knowledge” and the paradigm of “Revelation Guiding Knowledge.” The results show that the integration of Islamic sciences has the potential to create a holistic understanding that answers the challenges of the times, strengthens Islamic identity, and provides solutions to contemporary problems. This research recommends a multidimensional approach to build synergy between Islamic values and modern science for the progress of the people.